Analisis Kelangkaan Pupuk Bersubsidi Dan Faktor-Faktor Preferensi Penggunaan Pupuk Bersubsidi Petani Padi Di Kecamatan Insana Utara Kabupaten Timor Tengah Utara (Studi Kasus Desa Oekolo) - Monika Sonbay Afeanpah, Melania; Taena, Werenfridus; Putra Sipayung, Boanerges; Joka , Umbu (Paradigma Agribisnis, 2024)
The use of fertilizers by rice farmers in Oekolo Village is subsidized fertilizer provided by the government. The types of subsidized fertilizers provided are Urea and NPK. Urea and NPK fertilizers experience a shortage of fertilizers at certain times. This study aims to determine the scarcity of subsidized fertilizers and preferences for purchasing and using subsidized fertilizers for rice farmers in Oekolo Village. Data collection techniques in this study are primary data and secondary data. The population in the study was 260 people and the samples were taken using purposive sampling method as many as 150 people. The analysis used in this research is descriptive analysis and logistic regression analysis. The results of the analysis of this study indicate that education, experience, land area, subsidized fertilizer proposals in the RDKK do not match the amount of distribution, the dose of subsidized fertilizer use is not as recommended, and the pattern of fertilizer distribution affects the scarcity of subsidized fertilizer for rice farmers in Oekolo Village. Logistic regression analysis for the purchase of subsidized fertilizers shows that the variables of land area, access to information, and the right six have a significant effect on preferences for purchasing subsidized fertilizers, while the results of logistic regression analysis for the use of subsidized fertilizers show that the variables of education, land area, and access to information have a significant effect on preferences. the use of subsidized fertilizers for rice farmers in Oekolo Village.Keywords: Scarcity, Use, Subsidized Fertilizer, Food